Screening and eradication of Helicobacter pylori for gastric cancer prevention: the Taipei global consensus - Liou, Jyh-Ming; Malfertheiner, Peter; Lee, Yi-Chia; Sheu, Bor-Shyang; Sugano, Kentaro; Cheng, Hsiu-Chi; Yeoh, Khay-Guan; Hsu, Ping-I; Goh, Khean-Lee; Mahachai, Varocha; Gotoda, Takuji; Chang, Wei-Lun; et al. (Gut, 2020)
ObjectiveA global consensus meeting was held to review current evidence and knowledge gaps and propose collaborative studies on population-wide screening and eradication of Helicobacter pylori for prevention of gastric cancer (GC).Methods28 experts from 11 countries reviewed the evidence and modified the statements using the Delphi method, with consensus level predefined as ≥80% of agreement on each statement. The Grading of Recommendation Assessment, Development and Evaluation (GRADE) approach was followed.ResultsConsensus was reached in 26 statements. At an individual level, eradication of H. pylori reduces the risk of GC in asymptomatic subjects and is recommended unless there are competing considerations. In cohorts of vulnerable subjects (eg, first-degree relatives of patients with GC), a screen-and-treat strategy is also beneficial. H. pylori eradication in patients with early GC after curative endoscopic resection reduces the risk of metachronous cancer and calls for a re-examination on the hypothesis of ‘the point of no return’. At the general population level, the strategy of screen-and-treat for H. pylori infection is most cost-effective in young adults in regions with a high incidence of GC and is recommended preferably before the development of atrophic gastritis and intestinal metaplasia. However, such a strategy may still be effective in people aged over 50, and may be integrated or included into national healthcare priorities, such as colorectal cancer screening programmes, to optimise the resources. Reliable locally effective regimens based on the principles of antibiotic stewardship are recommended. Subjects at higher risk of GC, such as those with advanced gastric atrophy or intestinal metaplasia, should receive surveillance endoscopy after eradication of H. pylori.ConclusionEvidence supports the proposal that eradication therapy should be offered to all individuals infected with H. pylori. Vulnerable subjects should be tested, and treated if the test is positive. Mass screening and eradication of H. pylori should be considered in populations at higher risk of GC.